The Use of Soft Matrices on Soft Multisets and their Applications in Optimal Decision Process - Coskun, Arzu Erdem; Aras, Cigdem Gunduz; Sonmez, Ayse (Univ Nis, Fac Sci Math, 2018)
In this paper, we introduce a concept of a soft matrix on a soft multiset, and investigate how to use softmatrices to solve decisionmaking problems. An algorithmfor a multiple choose selection problem is also provided. Finally, we demonstrate an illustrative example to show the decision making steps.
3rd International Conference on Analysis and Applied Mathematics (ICAAM) -- SEP 07-10, 2016 -- Almaty, KAZAKHSTAN
Keywords: Sequences; series; summability; continuity; soft matrix; soft multiset